Prevalence and determinants of women's satisfaction on the quality of safe abortion service in Northwest Ethiopia - Kiros Terefe Gashaye; Asefa Adimasu Taddese; Tilahun Yemanu Birhan (BMC, 2022)
Abstract Background The standard of treatment in developing countries is harmed by a complex political landscape, an uncertain economic climate, rapid population growth, and clients are constantly complaining about the poor health system. Patients' assessments of the benefits and shortcomings of the service provided to them are expressed as satisfied or dissatisfied. The objective of this study was to determine the magnitude of women's satisfaction on quality of safe abortion and factors associated with it in Northwest Ethiopia. Methods Institution-based cross-sectional study design was done to collect data from 618 women in the selected health facilities in Northwest Ethiopia. Women having the gestational trophoblastic disease (partial mole) and those who cannot hear or are seriously ill during the data collection period were excluded. The study subjects were chosen using a randomization process, and each participant was questioned after receiving all necessary abortion treatment and giving verbal consent. Both bivariable and multivariable logistic regression analysis was carried out to determine covariates significantly associated with women's satisfaction on quality of abortion. Results The highest proportion of women who were reasoned out to terminate the fetus in the current pregnancy was due to financial problems (29.36%) and partner coercion (23.85%). Client satisfaction with safe abortion services in the study region was 25.10% (95% CI; 21.81-28.70). Women were 53.2% satisfied with the art of treatment/interpersonal abilities, 59.2% satisfied with the professional quality of care professionals, 54.5% satisfied with the physical environment, and 49.8% satisfied with the structure of the health care system, respectively. In the multivariable logistic regression analysis, women's living solely 0.47(0.26-0.87) & living with 2 to 4 people 0.11(0.04-0.29), college and above level of education 1.78(1.01-3.15), wanted the status of pregnancy 0.44(0.23-0.85) and post-abortion contraceptive users 1.70(1.01-2.89) were factors significantly associated with women's satisfaction level. Conclusion In this study, one-fourth of the women were satisfied with the quality of safe abortion services. Family size, women's educational status, maternity status, and post-abortion contraception use were predictors of women's satisfaction with the quality of abortion. Ethiopia's government should concentrate on addressing contraception needs in order to prevent women from having multiple abortions.